Panel Discussion In Honor of Dr Tom Waters The NIOSH Lifting Equation - Part I: A Review of Its Validation and Implications for Interpretation. (September 2016) - Fox, Robert R.; Maynard, Wayne S.; Kapellusch, Jay M.; Allread, W. Gary; Potvin, Jim; Fernandez, Jeffrey E.
The NIOSH Lifting Equation, specifically the 1991 Revised Lifting Equation or RLE (Waters et al., 1993) is used worldwide by occupational ergonomists, industrial engineers and safety specialists to assess and (re)design manual lifting tasks and industrial systems that involve either single or repetitive lifting. Since the initial publication of the RLE, there have been a number of published studies on its usability, effectiveness and validation. The purpose of this panel discussion will be to critically review these RLE-related studies and examine implications of applying the RLE in various occupational settings and working populations. The first of four presentations will summarize recent epidemiological studies that have quantified exposure-response relationships between the RLE and incidence of low-back pain-related care and medication use issues, and discuss the RLE implications for job surveillance, intervention, and design approaches. The second presentation discusses practical relevance of the RLE and issues surrounding its sensitivity and specificity in correctly identifying hazardous lifting tasks. The third presentation will critically examine the conservativeness of the recommended weight limit derived from RLE by comparing the output of the RLE with the output from the specific biomechanical, psychophysical and physiological criteria utilized in its initial development of the lifting equation. Although application of the RLE has exponentially grown since its inception, the final presentation explores its feasibility in applying it to a non-US work force. The primary audience for this session will be occupational ergonomists who utilize the NIOSH equation for job assessment and (re)design, although the discussion should be of interest to researchers as well. The overall goal of this Part 1 symposium is to provide RLE users with some practical suggestions and recommendations.